Diagnostic reference levels for the most frequent radiological examinations carried out in Brazil. - Freitas, Marcelo B.; Yoshimura, Elisabeth M. (Pan American Journal of Public Health, 2009)
Objectives. A large-scale survey of doses to patients undergoing the most frequent radiological examinations was carried out in health services in São Paulo (347 radiological examinations per 1000 inhabitants), the most populous Brazilian state. Methods. A postal dosimetría kit with thermoluminescence dosimeters was used to evaluate the entrance surface dose (ESD) to patients. A stratified sampling technique applied to the national health database furnished important data on the distribution of equipment and the annual number of examinations. Chest, head (skull and sinus), and spine (cervical, thoracic, and lumbar) examinations were included in the trial. A total of 83 rooms and 868 patients were included, and % 415 values of ESD were measured. Results. The data show large coefficients of variation in tube charge, giving rise to large variations in ESD values. Also, a series of high ESD values associated with unnecessary localizing fluoroscopy were detected. Diagnostic reference levels were determined, based on the 75th percentile (third quartile) of the ESD distributions. For adult patients, the diagnostic reference levels achieved are very similar to those obtained in international surveys. However, the situation is different for pediatric patients: the ESD values found in this survey are twice as large as the international recommendations for chest radiographs of children. Conclusions. Despite the reduced number of ESD values and rooms for the pediatric patient group, it is recommended that practices in chest examinations be revised and that specific national reference doses and image quality be established after a broader survey is carried out. Reprinted by permission of the publisher.